MANAJEMEN STRATEGIK PROGRAM LITERASI DI MADRASAH ALIYAH DARUT TAQWA - Nela Putri Ainuurohmah; Achmad Yusuf; Achmat Mubarok; Moh. Kholil Baita Putra (TARBIYA ISLAMIA : Jurnal Pendidikan dan Keislaman, 2023)
The literacy program at Madrasa Aliyah Darut Taqwa is the flagship program of the madrasa. The school or madrasah literacy program is one of the important programs that must be formulated using strategic management concepts. Strategic management helps organizations formulate better strategies. In this case strategic management is very important in the literacy program, therefore the author wants to know more about the strategic management literacy program at MA Darut Taqwa through, formulation literacy program strategies, strategic implementation literacy programs, and evaluation of literacy program strategies madrasa aliyah Darut Taqwa. The type of research used is descriptive qualitative research. The data and data sources used are secondary data and primary data. Data collection techniques used are (a). Observation, (b). Interview, (c). Documentation. The results of the study show that, 1) The strategic formulation of the literacy program implemented in Madrasah Aliyah Darut Taqwa is carried out through the formulation of program objectives, vision and mission, swot analysis, program implementation plans, short-medium-long term goals, identifying internal and external factors that can influence program; 2) The strategic implementation of the literacy program at Madrasa Aliyah Darut Taqwa is currently carried out through determining policies, providing motivation, and carrying out useful habits to develop the culture of the literacy program; 3) Strategic evaluation of the literacy program at Madrasah Aliyah Darut Taqwa is carried out with activity evaluation meetings carried out by the entire literacy driving team, then carrying out evaluation standards on planned targets, and standard results or product feasibility